Gaps between market performance, government planning and social objectives: projections and comparisons of carbon price intervals - Xing Zhou; Jianze Xu; Ming Zhang; Anyi Niu; Chuxia Lin (Humanities & Social Sciences Communications)
Abstract The core function of the carbon market is price discovery, but the current carbon prices neither reflect government planning to reduce emissions nor provide the necessary incentives for the innovation of low-carbon technologies in society. This study developed the Hubei carbon price probability forecasting models using machine learning and stochastic analysis from the perspectives of market performance, government planning, and social objectives. The carbon price interval expected by the government is slightly higher than that indicated by market performance, so there still exists a significant gap compared to the incentives required for innovation in low-carbon technologies. To fall within the 90% highest posterior density interval of the shadow price, it would need to be increased by at least 33 times. The differences in price intervals between the different perspectives are crucial for the government to address, as they reflect the complex interplay between environmental ambition, operational decisions and political acceptability.